2019
DOI: 10.1108/ir-05-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

A reconfigurable multi-mode walking-rolling robot based on motor time-sharing control

Abstract: Purpose The purpose of this paper is to put forward a nvew reconfigurable multi-mode walking-rolling robot based on the single-loop closed-chain four-bar mechanism, and the robot can be changed to different modes according to the terrain. Design/methodology/approach Based on the topological analysis, singularity analysis, feasibility analysis, gait analysis and the motion strategy based on motor time-sharing control, the paper theoretically verified that the robot can switch between the four motion modes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Through the gait analysis of the above locomotion modes, the robot can realize four locomotion modes by time-sharing control of the motor [27].…”
Section: Gait Switching Strategies For Four Locomotion Modesmentioning
confidence: 99%
“…Through the gait analysis of the above locomotion modes, the robot can realize four locomotion modes by time-sharing control of the motor [27].…”
Section: Gait Switching Strategies For Four Locomotion Modesmentioning
confidence: 99%
“…To adjust the posture and enlarge the working space of legged modules to enhance the obstacleclimbing capability, the trunk mechanism can be reconfigured into a steering four-bar linkage in steering motion with the aid of the singular feature. Liu et al (2020) put forward a new reconfigurable multi-mode walking-rolling robot based on the single-loop closed-chain four-bar mechanism, which has four types of motion modes: four-bar walking, four-bar rolling, self-deforming, and six-bar rolling modes. And the robot can be changed to different modes according to the terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2019aZhang et al ( , 2019b proposed a 3-RSR self-deformable multi-mode mobile parallel mechanism with rolling and self-traversing characteristics. Liu et al (2019) reported a four-bar mobile robot based on a singleloop kinematic chain. In summary, the above mentioned robots can realize self-reorganization in complex environments through self-deformation, reconfiguration, etc., so as to achieve obstacle crossing and mobile; it has the advantages of simple structure, easy control, strong environmental adaptability, etc.…”
Section: Introductionmentioning
confidence: 99%